Thermal quantum discord in Heisenberg models with Dzyaloshinski-Moriya interaction - 王林成 闫俊彦 衣学喜 (Chinese physics B, 2011)
We study the quantum discord of the bipartite Heisenberg model with the Dzyaloshinski-Moriya （DM） interaction in thermal equilibrium state and discuss the effect of the DM interaction on the quantum discord. The quantum entanglement of the system is also discussed and compared with quantum discord. Our results show that the quantum discord may reveal more properties of the system than quantum entanglement and the DM interaction may play an important role in the Heisenberg model.